Proceso de atención de enfermería en paciente con 55 años con diagnóstico de enfermedad Covid- 19. - Sala Medina, Alejandra Margarita (2023)
The coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome virus type-2 (SARS-CoV-2), was declared a pandemic in March 2020.Fatality rates are estimated between 1% and 3%, mainly affecting older adults and those with comorbidities, such as hypertension, diabetes, cardiovascular disease and cancer. (Díaz Castrillón & Toro Montoya, 2020). The average incubation period is 5 days but can be up to 14 days. Many infected patients are asymptomatic; however, because they release large amounts of virus, they are a permanent challenge to contain the spread of infection, causing the collapse of health systems in the most affected areas. Topics such as the pathogen, etiology, clinical manifestations, diagnosis, and treatment are addressed. (Díaz Castrillón & Toro Montoya, 2020). This clinical case focuses on a 55-year-old male patient, who was admitted to the emergency area due to general malaise (myalgia), chest tightness, shortness of breath, dry cough of several days of evolution, hyperthermia, pain throat, headache, loss of sense of smell (anosmia) and taste (dysgeusia), saturating 86%. He is evaluated by the treating physician and diagnosed with bilateral pneumonia and positive COVID19 PCR in nasopharyngeal exudate. So he is referred to the Intensive Care Unit with respiratory failure.